Internal Control Systems and Utlization of Local Revenue in Tororo Municipal Council Eastern Division - Miriam Apaama (Uganda Christian University, 2025)
The study was about internal control and local resource utilization in TMC, Eastern Division. The major purpose of this study was to identify the effect of internal control on local resource usage in TMC, Eastern Division. To achieve this purpose the study was guided by three set objectives: To identify the different sources of local revenue in TMC, Eastern Division; to identify the internal controls in TMC, Eastern Division; to identify relationship between internal control and local resource utilization. The methods used in obtaining primary data included: self-administered questionnaire, secondary data was obtained through secondary data sources; internal Reports, among others. The sampling technique used was simple random and purposive sampling and with descriptive data analysis. Findings reveal the following: objective one results show significantly high positive relationship between revenue bases and utilization; objective two results show that internal controls explain the variation in the local resource utilization up to 10.2%, and remaining 89.8% are for other factors other than internal controls, and further influence LR utilization by 31.9% as shown by Beta value (0.319); objective three. The results reveal that there is a significant and statistically positive relationship between internal controls and the local revenue utilization based on Pearson correlation coefficient 39.0% as represented by (r=0.390) at a significant level of 1% also (0.01). Recommendations: Need to improve on the legislation, laws be read and understood by the residents and staff, parliament to make laws for the Local Government, Re-engineer the entire Local Government systems, Monitoring and evaluation be done by qualified persons, independent persons to review the laws and plans, and government to evaluate Local Governments based on cost benefit analysis.